POD Analysis of Flow Field Characteristics of Jet Oscillators with Different Length-to-Diameter Ratios - Shijin FAN; Haiping TIAN; Guozhen MA; Minhui GUO (气体物理, 2025)
The alteration of geometric parameters of the jet oscillator influences its flow characteristics. Elucidating the underlying flow physics from a fluid dynamics perspective is beneficial in guiding the optimization design direction for the jet oscillator structure. This study aimed to reveal the specific impact of the length-to-diameter ratio on the flow field of the jet oscillator. The flow field of the jet oscillator was numerically simulated, showcasing the periodic evolution process of the flow field under different length-to-diameter ratios. Additionally, the obtained flow field was subjected to proper orthogonal decomposition (POD) to extract the first four POD modes of the flow field along with the corresponding time coefficient evolution curves. Research indicates that the periodic evolution of the main vortex structures inside and outside the flow field of the jet oscillator with different length-to-diameter is similar, while the performance of feedback vortices differs from that of small-scale vortex bubbles. The first two POD modes under different operating conditions exhibit attached-wall main vortex and vortex transition modes. The antisymmetric characteristics of the latter two modes cease to manifest when the length-to-diameter ratio increases to 3.5. Throughout the cycle, the jet oscillator flow field demonstrates varying flow characteristics due to the dominance of different modes at different stages. Spectral analysis of the time coefficient curves reveals that with increasing length-to-diameter ratio, the fundamental frequencies of the modes for each operating condition gradually decrease, while the composition of higher-order mode frequencies becomes more complex, leading to a weakening of regularity.